Effects of venezuelan migration on citizen security in Metropolitan Lima - Ponce de Leon, Olger Benavides (2020)
The objective of this research was to identify the reasons that have led to the impact of Venezuelan migration in Peru on citizen security in Metropolitan Lima, as well as to understand the experiences of Venezuelan migrants and to assess the actions of the National Police to address citizen insecurity. Likewise, this research was descriptive and empirical, with a qualitative approach, and the method used was ethnomethodology. The design was non-experimental and transversal. The population consisted of police officers and citizens in general, while the sample was made up of police officers working in the area of immigration and divisions of the Criminal Investigation Department and, additionally, citizens living in Metropolitan Lima. The data collection techniques and instruments were direct observation, interview and document review, and the questionnaire. Finally, the Atlas-Ti program was used for data analysis. It was concluded that migration generates demographic transitions that affect crime rates, since as the flow of migrants increases, the proportion of the population with a crime-prone profile increases; in turn, crime rates of victimization and perception of citizen insecurity have increased in the country as a result of the massive exodus of Venezuelans, generating impact and anxiety in the national society.